Mapping the User Experience: Development of a Validated Instrument from the Plans and Scripts of the Computer Community of Practice - Lehane, Pat (Human Technology, 2012)
A plethora of surveys for assessing computer use for usability or technology acceptance exist today. This article discusses the Systems Acceptance Indicator, a validated survey instrument for assessing the user experience from a cognitive–ergonomic perspective. The action research discussed in this paper utilized grounded theory analysis to establish the data-driven emergent theoretical constructs that provided the system acceptance categories (criteria) for the survey. These data-driven emergent theoretical constructs were the basis for the proposed theoretical abstraction hierarchy of the survey criteria. Principle component analysis of the survey data produced an abstraction hierarchy identical to the theoretical model. This result confirmed the alignment of the human–computer interaction theoretical constructs with the data-driven emergent theory. The intent behind the human–computer interaction theoretical rationale for the emergent abstraction hierarchy was to provide a consistent and repeatable interpretation of the user response to the survey.